PENGGUNAAN Beauveria bassiana DAN Bacillus thuringiensis UNTUK MENGGENDALIKAN Plutella xylostella L.(Lepidoptera; Plutellidae) DI LABORATORIUM - Ria Febrika1*, Syahrial Oemry2, Mena Uly Febrika; Syahrial Oemry; Uly Uly Tarigan (Jurnal Agroekoteknologi, 2014)
ABSTRACTResearch on title the utility beauveria bassiana and bacillus thuringiensis to controlplutella xylostella L. (lepidoptera: plutellidae) in the laboratory. The research was to study theeffectivity of B. bassiana and B. thuringiensis as biological agens to control P. xylostella oncabbage in laboratory. The research was conducted at the Insect Laboratory, Agriculture Faculty,University of Sumatera Utara, Medan since May–December 2012. The method of this research wasRandomized Complete Design Non Factorial with seven treatments (control, B. thuringiensis 5 g/l,B. thuringiensis 10 g/l, B. thuringiensis 15 g/l,B. bassiana 5 g/l, B. bassiana 10 g/l, B. bassiana15 g/l) with three replications. The parameters were the percentage of mortality and the change ofmorphology larva. The results showed that B. thuringiensis and B. bassiana effective to controlP. xylostella, the using of B. thuringiensis result the highest percentage of mortality was 93.33% on10 g/l and the lowest was 53.33% on 5 g/l, the using of B. bassiana result the highest percentage ofmortality was 86.67% on 10 g/l and the lowest was 53.33% on 5 g/l.Keywords : Plutella xylostella, Beauveria bassiana, Bacillus thuringiensis